Te Deum Laudamus : Orgelprofessorn från Piteå spelar musik av Buxtehude, Bach och Tournemire (Örnsköldsvik : Orgelklubben vox humana, 2015)
The festival "Orgelspelen i Örnsköldsvik" is a regularly recurring event, sponsored by many organizations and administered by the group of organists called "Vox humana", which this year included two solo organ recitals by Gunnar Idenstam and Gary Verkade. PROGRAM Dieterich Buxtehude 1637-1707 PRAELUDIUM i d, BuxWV 140 I Godkänd; 2015; 20151202 (gave)